Sleep quality in people with multiple sclerosis (Revista Contexto & Saúde, 2026)
Introduction: Multiple sclerosis is a chronic neurological autoimmune condition marked by damage to the myelin sheath, resulting in impaired transmission of nerve impulses and a wide range of symptoms, including sleep disorders. Objectives: to assess sleep quality in people with MS according to the parameters established by the Mini Sleep Questionnaire and based on the participants' own perceptions. Method: quantitative, qualitative, descriptive, and exploratory research conducted in a virtual environment. Data collection took place between March and April 2023 through the following instruments: 1) Sociodemographic and clinical characterization; 2) Mini Sleep Questionnaire; 3) Guiding questions. Quantitative data were analyzed and presented descriptively, while qualitative data were examined through Thematic Analysis. Results: A total of 56 people with multiple sclerosis participated, mostly women, white, between 18 and 39 years old. Most reported relapsing-remitting multiple sclerosis, with up to five years since diagnosis, and were undergoing pharmacological treatment. The most frequent symptoms included tingling, weakness, walking difficulties, and urinary or intestinal dysfunction. Forty-seven participants presented sleep-related difficulties, among whom 7 had mild sleep difficulty, 7 moderate, and 33 severe sleep difficulty. Three thematic categories were identified: “Sleep quality as perceived by people with multiple sclerosis”; “Pharmacological strategies related to sleep quality adopted by people with multiple sclerosis”; and “Nonpharmacological strategies related to sleep quality adopted by people with multiple sclerosis”. Conclusion: People with multiple sclerosis exhibit sleep disturbances and employ strategies aimed at improving sleep quality.
Keywords: Multiple Sclerosis; Nervous System Diseases; Sleep; Sleep Quality; Health Strategies